Analis dampak pandemi Covid 19 terhadap pendapatan pengusaha usaha rumah makan dan faktor-faktor yang mempengaruhinya di Kota Jambi - Maulidia Imastary Tan; Syamsurijal Tan; Istiqomah Malinda SB (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
In general, this study aims to analyze the impact of the COVID-19 pandemic to the income of Restaurant Business in Jambi City. Specifically, the objectives can be formulated in four objectives, namely: 1) To test whether there is a difference in the income of the Restaurant Business before and during the Covid 19 Pandemic; dan 2) To calculate and analyze the factors that affect Restaurant Business Income in Jambi City. The data used is sourced from a survey on restaurant businesses in Jambi City in 3 districts, namely Telanaipura District, Kota Baru District, and Pasar District. The analytical tools used are descriptive statistics and multiple linear regression. The results of the research are : 1), sturtup capital, working time, long effort, and total family burden has significan influence to restaurant business income, while operating capital and education is not significanly.